Willingness to whistle blow among Muslim consumers - Abdul, Mohani; Ismail, Hashanah; Hashim, Haslina; Mohd Yusof, Mastura (David Publishing Company, 2011)
The paper reports on a qualitative study using three focus groups drawn from Muslim consumers both local and foreign. Respondents were given vignettes depicting unethical halal claims scenarios to which respondents were required to respond. Two Malaysian consumer groups responded by declaring that they will whistle blow by reporting the matter to a religious authority, the Islamic Development Department (JAKIM), while another group that consists of six Muslim foreign students will just leave the business premise without making any complaints to any authority. The different course of actions taken could be explained by the diverse background of the Malaysian population and their level of awareness in selecting their halal food and their high degree of intolerance to such practice whilst the level of tolerance among foreign Muslim respondents might be different from their Malaysian counterparts or that they have never encountered such a problem before they came to Malaysia. The study also reports the response from JAKIM in relation to the relevant channels for whistle blowing regarding misleading halal labels.